Hemocompatibility properties of a polymer surface treated in plasma containing sulfur. (19th February 2016) - Vesel, Alenka; Zaplotnik, Rok; Modic, Martina; Mozetic, Miran
Abstract : Polymer polyethylene terephthalate was treated in plasmas containing sulfur to incorporate different sulfur functional groups and improve its hemocompatibility properties. Plasma was created either by SO2, H2 S or an H2 S/O2 mixture. Sequential treatments in H2 S and O2 plasmas were also used. The surface of the treated samples was analyzed using X‐ray photoelectron spectroscopy, and surface hemocompatibility was tested by investigating platelet adhesion. While SO2 plasma caused functionalization of the surface with –SO3 and –SO4 functional groups, H2 S plasma caused functionalization with non‐oxidized –SH2 sulfur groups, as well as sulfur deposition on the polymer surface. Addition of oxygen to the H2 S gas caused a significant decrease in the amount of sulfur on the polymer surface and only minor sulfur oxidation. This observation led to the conclusion that added oxygen removed/prevented sulfur deposition on the polymer surface. Enhanced results were obtained by a sequential treatment in H2 S and then O2 plasma, where oxidation of sulfur and formation of –SO and –SO2 functional groups were observed. The O2 plasma exposure had to be short enough to prevent the unwanted removal of sulfur from the surface. High platelet adhesion was observed for all plasma‐treated surfaces. Copyright © 2016 John Wiley & Sons, Ltd.